Factors associated with sexual dysfunction in Taiwanese females with rheumatoid arthritis. Issue 1 (December 2017) - Lin, Miao-Chiu; Lu, Ming-Chi; Livneh, Hanoch; Lai, Ning-Sheng; Guo, How-Ran; Tsai, Tzung-Yi
Abstract Background Patients with rheumatoid arthritis (RA) may experience sexual dysfunction because of symptoms or adverse effects from treatments. Data on female sexual dysfunction (FSD) in Asian females with RA issue are limited. This study investigated the prevalence and factors associated with FSD in Taiwanese patients with RA. Methods This cross-sectional study used a purposive sampling method to recruit 195 females with RA from a single hospital in southern Taiwan. Demographic and clinical characteristics were obtained by review of medical records and a structured questionnaire. The Chinese version of the Female Sexual Function Index and the Taiwanese Depression Questionnaire were also administered. Multiple logistic regression analysis was used to identify factors associated with FSD. Results The crude and age-standardized prevalence of FSD were 66.8% and 48.2%, respectively. Patients who were older, with a comorbid condition, with more depressive symptoms, and with greater disease activity had a significantly higher risk of FSD. Conclusion Our findings indicate that FSD is more common in Taiwanese individuals with RA who have certain specific demographic and clinical characteristics. These findings may help to identify and facilitate the provision of appropriate interventions to ensure better sexual health in female patients with RA.